Daoism in Modern China: Clerics and Temples in Urban Transformations,1860-Present - Goossaert, Vincent (Routledge Studies in Taoism Ser., 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- Acknowledgments -- Notes on contributors -- Introduction -- Part I Historical overview -- Chapter 1 Urban Daoists, from 1860 to the present -- Chapter 2 The Martial Marquis Shrine: politics of temple expropriation and restitution, and struggles of Daoist revival in contemporary Nanyang -- Part II Spirit-writing temples and their networks -- Chapter 3 The Jin'gaishan network: a lay Quanzhen Daoist organization in modern Jiangnan -- Chapter 4 The Dao in the Southern Seas: the diffusion of the L ü zu cult from Meizhou to Bangkok -- Part III Householder urban Daoists -- Chapter 5 The modern transformations of the Old Eastern Peak temple in Hangzhou -- Chapter 6 Zhengyi Daoists and the Baoqing Pier neighborhood in modern Hankou -- Index.